Failure to Remove Bluetongue Serotype 8 Virus (BTV-8) From in vitro Produced and in vivo Derived Bovine Embryos and Subsequent Transmission of BTV-8 to Recipient Cows After Embryo Transfer - Haegeman, Andy; Vandaele, Leen; De Leeuw, Ilse; Oliveira, André P.; Nauwynck, Hans; Van Soom, Ann; De Clercq, Kris (Frontiers in Veterinary Science, 2019)
The behaviour of BTV-8 in cattle is different from most other serotypes not only with regards to clinical signs but certainly with respect to virus transmission (transplacental, contact). Therefore, the possibility of virus transmission by means of embryo transfer was examined by in vitro exposure of in vitro produced and in vivo derived bovine blastocysts to BTV-8 followed by different washing protocols, including longer exposure times (up to 120 s) to 0.25% trypsin at room temperature or at 37°C. None of the washing protocols used was successful in removing the viral genome completely from the in vitro produced and in vivo derived embryos as was demonstrated by real-time PCR. Moreover BTV-8 virus was transmitted to recipient cows after embryo transfer of in vivo derived BTV8-exposed embryos, which had been subjected to routine decontamination as recommended by IETS, consisting of 5 washes in PBS followed by a double treatment of 0.25 % trypsin for 45s at 37°C, and an additional 5 washes in PBS with 2% FCS. This study clearly demonstrates the necessity of vigorous application of the directives for screening of potential donors and the collected embryos, especially in regions with BTV-8, to prevent transmission of the disease.